2011
DOI: 10.1002/aoc.1777
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of diethyltin(IV) derivatives and their biological aspects as potential antitumor agents against Agrobacterium tumefacien cells

Abstract: A series of new diethyltin(IV) derivatives of substituted phenyl acrylates have been synthesized and characterized by elemental analysis, IR, multinuclear NMR ( 1 H, 13 C, 19 F and 119 Sn) and X-ray single crystal analysis. X-ray single crystal diffraction study of complex 8 has shown the formation of secondary O· · ·Sn, F· · ·H and H· · ·O intermolecular interactions. These complexes proved to be good antitumor agents. The antitumor properties are presumably due to the intercalative mode of interaction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The data is given in Tables 10 and 11 . It was found that the organotin(IV) complexes possessed significantly higher activity towards the tested organisms than the free ligands as reported earlier [ 12 , 14 , 35 ]. The coordination of the ligand with chlorodi- or triorganotin(IV) moieties has appreciably enhanced the activities of the product complexes.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The data is given in Tables 10 and 11 . It was found that the organotin(IV) complexes possessed significantly higher activity towards the tested organisms than the free ligands as reported earlier [ 12 , 14 , 35 ]. The coordination of the ligand with chlorodi- or triorganotin(IV) moieties has appreciably enhanced the activities of the product complexes.…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, organotin(IV) compounds have been tested for their in vitro activity against a large variety of tumor cell lines [ 14 ] and have been found to be as effective as or better than traditional heavy metal anticancer drugs such as cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and characterization of organotin(IV) complexes of Schiff base ligands have always attracted the attention of inorganic chemists and is well established in the literature [10][11][12][13][14]. Organotin(IV) complexes have been extensively studied due to their beneficial biological activities as well as their wide industrial and agricultural applications [15][16][17][18][19][20][21]. de Sousa et al have reported organotin(IV) derivatives of 2hydroxyacetophenone-N(4)-phenylthiosemicarbazone and found that the Sn(IV) atom adopts a strongly distorted trigonal bipyramidal configuration [22].…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of organotin compounds is greatly influenced by the structure of the molecule, molecular mass and conceivably by the nuclearity. The role of a ligand is also quite significant in transportation of organotin moiety to the site of action …”
Section: Decomposition Kineticsmentioning
confidence: 99%